Impact of Thermal Ageing and Multiple Reflow on Lead Free Composite Solder : A Short Review. Issue 1 (October 2020) - Zaimi, Nur Syahirah Mohamad; Salleh, Mohd Arif Anuar Mohd; Abdullah, Mohd Mustafa Al Bakri; Mostapha, Marliza; Ahmad, Romisuhani
Abstract: This paper reviews the impact of the thermal ageing and multiple reflow to the intermetallic compound (IMC) layer and mechanical performance of lead free solder reinforced with various reinforcements. Based on available literatures it had been proved that, the IMC layer and mechanical properties can be affected with the exposure of different temperatures and time. Besides that, the incorporation of the reinforcement in the matrix of solder alloys could improve the thickness of IMC layer and strength of the solder joints although it had been subjected to thermal ageing and multiple reflow cycles as compared to unreinforced solder. Therefore, the composite solder system could be possibly applied and adapted in current electronic devices even with the exposure of high temperatures.